Quality of life in patients with rheumatoid arthritis during rituximab therapy - Tatiana Alekseyevna Raskina; M V Koroleva (Современная ревматология)
Objective: to evaluate the effect of rituximab (RTM) on quality of life (QL) in patients with rheumatoid arthritis (RA) from the results of EQ-5D questionnaire total scores. Subjects and methods. Ninety-eighty patients with a valid diagnosis of RA were followed up. All the patients were randomized to two groups according to the basic therapy option: 1) 56 patients on combination therapy with methotrexate (MT; mean dose 13.72±0.06 mg weekly) and rituximab (RTM) by the standard regimen; 2) 42 patients receiving only MT (mean dose 12.6±0.08 mg weekly). The follow-up was 24 months. The international EQ-5D questionnaire was employed to assess QL. Results. While filling out the EQ-5D questionnaire, all the patients with RA mentioned baseline health problems to one extent or another. One year after therapy, there was a statistically significant increase in health index in both Groups 1 and 2: 0.61±0.04 and 0.63±0.07 (р<0.05 and р<0.05, respectively). Group 1 showed a statistically significant rise in VAS scores at 12 (46.7±6.3 mm; р<0.05) and 24 (49.3±11.4 mm; р<0.05) months versus at baseline. Conclusion. There was a satisfactory therapeutic effect only in the MT + RTM combination group whereas there was a minimal one in the MT monotherapy group.